Asian Yearbook of International Law, Volume 2 (1992) - Swan Sik, Ko; Syatauw, J.J.G; Pinto, M.C.W (Asian Yearbook of International Law, 1994)
The Asian Yearbook of International Law is a major refereed publication dedicated to international law issues as seen primarily from an Asian perspective. Readership: Academics and practitioners who deal with international public law in Asia will appreciate this unique, complete resource. The Asian Yearbook of International Law provides insight into Asian views and practices, especially for non-Asian readers, and also promotes the dissemination of knowledge of international law in Asia.